Gender Inequality and Economic Growth in Aceh: Evidence from Panel Data Analysis - M. Saleh; Suriani Suriani; M. Shabri Abd. Majid (Grimsa Journal of Business and Economics Studies, 2026)
This study examines the impact of gender inequality on economic growth in Aceh Province, Indonesia, where persistent gender disparities may hinder regional economic performance by limiting human capital development and economic participation. Despite increasing attention to gender issues in Indonesia, empirical evidence for Aceh remains limited. Using panel data from 23 districts/cities in Aceh Province during 2018-2025, this study employs a random effects model to analyze the effect of the Gender Inequality Index on economic growth. The analysis also incorporates control variables, including the open unemployment rate, labor force participation rate, and human development index. The empirical findings reveal that gender inequality has a negative and statistically significant effect on economic growth in Aceh, indicating that higher levels of gender inequality tend to reduce regional economic performance. These findings imply that reducing gender inequality is essential for achieving sustainable and inclusive economic growth. Therefore, policymakers should strengthen gender-inclusive development policies, expand women’s access to education and employment opportunities, and encourage greater female participation in economic activities to support long-term regional development.